1995
DOI: 10.1001/archinte.1995.00430020022004
|View full text |Cite
|
Sign up to set email alerts
|

Management of Cardiac Arrhythmias With Radiofrequency Catheter Ablation

Abstract: Radiofrequency energy has emerged as the current energy source of first choice for ablation procedures. We review the development of radiofrequency energy for ablation procedures and its advantages and disadvantages. We also review how radiofrequency energy can be applied to treat various arrhythmias. We also discuss some of the insights that catheter ablation has in turn provided in our understanding of arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 143 publications
0
3
0
Order By: Relevance
“…In addition to its cardiac-depressant effects [1][2][3], propofol has been reported to cause profound sinus bradycardia and atrioventricular (AV) block [4][5][6][7][8][9]. However, only lim ited data exist regarding its electrophysiological proper ties [10], Several commonly administered anesthetic agents in fluence cardiac conduction by a variety of mechanisms, including direct electrophysiological effects, neurally me diated changes in autonomic nervous system tone, and indirect electrolyte and acid-base changes that accompa ny spontaneous and controlled ventilation [11], With the advent of catheter ablation procedures to treat cardiac tachyarrhythmias [12], anesthesiologists are often asked to provide sedation and, in selected patients, general anes thesia during such procedures [13], Reliable assessment of changes in the conduction properties of cardiac tissues is important during catheter ablation, and, therefore, ideal ly, the anesthetic agent used during the procedure should have a minimal or no effect on cardiac conduction proper ties. Since propofol is reported to cause bradyarrhythmias [4][5][6][7][8][9] and is frequently used in the electrophysiology labo ratory [13], we studied its electrophysiological effects in an attempt to elucidate the mechanism(s) whereby it pro duces bradyarrhythmias.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its cardiac-depressant effects [1][2][3], propofol has been reported to cause profound sinus bradycardia and atrioventricular (AV) block [4][5][6][7][8][9]. However, only lim ited data exist regarding its electrophysiological proper ties [10], Several commonly administered anesthetic agents in fluence cardiac conduction by a variety of mechanisms, including direct electrophysiological effects, neurally me diated changes in autonomic nervous system tone, and indirect electrolyte and acid-base changes that accompa ny spontaneous and controlled ventilation [11], With the advent of catheter ablation procedures to treat cardiac tachyarrhythmias [12], anesthesiologists are often asked to provide sedation and, in selected patients, general anes thesia during such procedures [13], Reliable assessment of changes in the conduction properties of cardiac tissues is important during catheter ablation, and, therefore, ideal ly, the anesthetic agent used during the procedure should have a minimal or no effect on cardiac conduction proper ties. Since propofol is reported to cause bradyarrhythmias [4][5][6][7][8][9] and is frequently used in the electrophysiology labo ratory [13], we studied its electrophysiological effects in an attempt to elucidate the mechanism(s) whereby it pro duces bradyarrhythmias.…”
Section: Introductionmentioning
confidence: 99%
“…It can produce accurately placed, small lesions in neurosurgery applications, 17,18 and can, in a similar manner, interrupt abnormal intracardioconduction pathways in cardiosurgery. 19,20 Conventional monopolar radiofrequency (RF) electrodes work well in these situations, because they can produce small and precise tissue necrotic points. Internally cooled RF electrodes, however, can create larger necrotic foci than conventional monopolar electrodes 21,22 and can, therefore, be used to destroy small tumors.…”
Section: Introductionmentioning
confidence: 99%
“…A few in vivo animal studies are discussed in situations where human-exposure studies are not available (e.g., acute effects of RFR). This paper does not address RFR ablation of heart tissue; this topic has been reviewed elsewhere (e.g., Manolis et al 1994;Wagshal et al 1995). [Recently, Simmers et al (1996) concluded that effects of RFR ablation are exclusively thermally mediated.]…”
Section: Introductionmentioning
confidence: 99%